Cultural Diplomacy of Thailand and Indonesia in the Philippines - Abuan, Romina Eloisa Manabat (Malaysian Journal of International Relations, 2021)
Cultural diplomacy, often overlapping with public diplomacy, is defined as the exchange of ideas, information, values, systems, traditions, beliefs, and other aspects of culture with the intent to foster mutual understanding, enhancing socio-cultural cooperation and promoting national interests between two or more States. The Philippines can be conceptualised as an arena for States to win hearts and minds through cultural diplomacy. This article focuses on Indonesia and Thailand. Indonesia, at a glance, is active in sharing its culture and language through the Bahasa Indonesia bagi Penutur Asing (BIPA) programme while Thailand is the first to practise ‘gastro diplomacy’ or tourism diplomacy. This paper tackles three questions: Firstly, how do Indonesia and Thailand’s respective foreign policy goals translate to cultural diplomacy set in the Philippines? Secondly, using the concept of soft power, why are Indonesia and Thailand actively practicing cultural diplomacy? And thirdly, what possible outcomes do Indonesia and Thailand seek to achieve from the cultural and educational events and programmes provided for and promoted by their embassies in the Philippines?